The prince of Broadway - Shupe, Joanna (Shupe, Joanna. Uptown girls., 2020)
As the owner of the city's most exclusive casino, Clayton Madden holds the fortunes of prominent families in the palms of his hands every night. There is one particular family he burns to ruin, however, one that has escaped his grasp . . . until now. Florence Greene is no one's fool. She knows Clayton Madden is using her to ruin her prestigious family . . . and she's using him right back. She plans to learn all she can from the mysterious casino owner--then open a casino of her own just for women. With revenge on his mind, Clay agrees to mentor Florence. However, she soon proves more adept--and more alluring--than Clay bargained for. When his plans are threatened, Clay must decide if he is willing to gamble his empire on love.